Knowledge levels of mothers with children aged 0-6 about autism spectrum disorder - Parlak, Mehmet Emin; Küçükkelepçe, Osman; Öz, Erdoğan; Özbey, Mehmet Yavuz; Kapıcı, Yaşar (The European Research Journal, 2023)
Objectives: In this study, it was aimed to measure the level of knowledge about autism spectrum disorder (ASD) in mothers of children aged 0-6 and to determine the necessity of informative studies on this subject and the characteristics of the group that should be focused on in future studies. Methods: The population of the study consisted of mothers with children aged 0-6 years who applied to the pediatric outpatient clinic. In order to measure ASD knowledge, 24 questions were created by scanning the literature. Results: 388 mothers were included in the study. There was a significant difference in educational status regarding ASD knowledge score (p = 0.042). There was a significant difference between economic status in terms of ASD knowledge score (p = 0.026). Those who had heard of ASD had a significantly higher ASD knowledge score than those who had not heard of ASD (p < 0.001). The ASD knowledge score of those who had acquaintances with ASD was significantly higher than those who had not (p = 0.001). There was a significant negative correlation between ASD total score, age, and first gestational age. Conclusions: Increasing the level of knowledge about ASD will enable early diagnosis and early intervention in the course of the disease and the rapid integration of individuals with ASD into society.